Early childhood educators' beliefs on increasing fundamental motor skills by playing games in a physical education context: The contradictory belief - Friskawati, Gita Febria; Ma’mun, Amung; Mahendra, Agus (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2023)
The development of fundamental motor skills (FMS) is crucial and should begin in early childhood. As of now, several early childhood educators in Indonesia, particularly in West Java, think that incorporating playground games into the classroom curriculum is the best course of action for raising children’s FMS. This study aimed to present statistics on FMS findings for early childhood who have incorporated physical activity into the curriculum and to demonstrate that these results are still in conflict with teachers’ beliefs. Ex post facto research was applied to one of the early childhood education pilot programs in West Java, Indonesia, including a total of 30 kids. This school’s long-standing intervention involves giving children 30 minutes of structured playtime and 30 minutes of unstructured playtime at the start of each learning period. The Test of Gross Motor Development-2 (TGMD-2) was used to measure FMS. The study’s findings showed that both boys’ and girls’ FMS in both locomotor and manipulating components of the movement were very lacking and inversely proportional to teachers’ belief who believe that this activity will improve children’s motor skills. It is recommended that physical education specialists accompany both structured and unstructured play programs conducted on school playgrounds so that the early childhood education curriculum's programs are properly validated to raise children's FMS following Developmentally Appropriate Practice (DAP).